Clinical Outcomes of the Polyvinyl Alcohol (PVA) Hydrogel Implant for Hallux Rigidus. (September 2020) - Eble, Stephanie K.; Hansen, Oliver B.; Chrea, Bopha; Cabe, Taylor N.; Garfinkel, Jonathan; Drakos, Mark C.; ,
Background: Hallux rigidus is a common arthritic condition that has been addressed surgically with a range of techniques, from an isolated cheilectomy to first metatarsophalangeal (MTP) joint fusion. Recently, hemiarthroplasty with polyvinyl alcohol (PVA) hydrogel implant has been used as an alternative treatment to relieve pain while preserving motion of the first MTP joint. We retrospectively reviewed patient-reported outcome scores and clinical outcomes for patients treated for hallux rigidus with PVA hydrogel implant at an academic, multisurgeon center. Methods: A total of 103 patients who underwent first MTP hemiarthroplasty with PVA hydrogel implant between January 2017 and October 2018 were retrospectively reviewed (average, 26.2 months). Eight surgeons were represented. Baseline Patient-Reported Outcomes Measurement Information System (PROMIS) scores for the Physical Function, Pain Interference, Pain Intensity, Global Physical Health, Global Mental Health, and Depression domains were collected prospectively and compared with PROMIS scores collected at a minimum of 1 year postoperatively (average, 13.9 months). Seventy-three patients had both preoperative and postoperative scores. Ten of these patients had undergone a prior procedure of the first MTP, and 52 underwent concurrent Moberg osteotomy at the time of PVA hydrogel implantation. Results: For patients with baseline and postoperative PROMIS scores, significant pre- to postoperative improvement was detected for the Physical Function, Pain Interference, Pain Intensity, and Global Physical Health domains ( P < .05). Patients who had undergone a prior procedure of the first MTP had significantly higher postoperative Pain Intensity scores compared with those who did not undergo a prior procedure. Patients undergoing concurrent Moberg osteotomy had significantly lower postoperative Pain Interference and Pain Intensity scores compared with those who did not undergo a Moberg. Two patients underwent revision procedures in the first 2 years postoperatively, one with revision hemiarthroplasty and one with conversion to arthrodesis. Conclusion: On average across our entire cohort, physical function and pain scores improved significantly pre- to postoperatively; however, postoperative pain scores were significantly higher for patients who had undergone a prior procedure of the first MTP and significantly lower for patients who underwent concurrent Moberg osteotomy. The implant displayed excellent survivorship in the first 2 years postoperatively, with only 2 revision procedures. Level of Evidence: Level III, comparative series.